Media Komunikasi Visual Mini Album Too Shy, Too Blind Band Magnolia Celebration - Hannan Hafizh Rizq (Penerbit dan Percetakan, CV. Picmotiv, 2024)
The music industry continues to be a popular form of entertainment today. The urgency of the problem faced in this research is how to create music popularity by utilizing technological advances that make music easily become famous among the public. problem solving plan by designing visual communication on the Magnolia Celebration mini album entitled